Believing in nothing and believing in everything: The underlying cognitive paradox of anti-COVID-19 vaccine attitudes. (April 2022) - Newman, Devora; Lewandowsky, Stephan; Mayo, Ruth
Abstract: A major reason why some people oppose the COVID-19 vaccine is the influence of misinformation. This study suggests that the cognitive paradox of simultaneously believing known facts less and new, "alternative facts" more is the outcome of a distrust mindset, characterized by spontaneous consideration of alternatives, including misinformation. We captured this paradox and its correlates in a scale that measures individuals' ability to distinguish between the truth value of well-established facts ("Earth rotates eastward around its own axis, completing a full rotation once in about 24 h") and baseless "alternative facts" ("Earth can change its rotation direction and flip its axis, and we will never notice it"). Assuming that an anti-COVID-19 vaccine attitude arises from a chronically distrusting mindset, we sampled participants on Prolific who were pre-screened for their COVID-19 vaccine attitude based on earlier responses. We found that people who rejected COVID-19 vaccines believed well-established facts less, and "alternative facts" more, compared to supporters of the vaccine. Less discernment between truths and falsehoods was correlated with less intellectual humility, more distrust and greater reliance on one's intuition. This observed thought pattern offers insights into theoretical understanding of the antecedents of belief in "alternative facts" and conspiracy theories. Highlights: We tested a cognitive paradox that could precede acceptance of misinformation. The paradox is skepticism of known claims but gullibility for "alternative facts". We find the paradox in opposers of the COVID-19 vaccine, but not in supporters of it. The vaccine attitude was pre-screened by Prolific, ruling out motivational biases. Correlated traits are distrust, reliance on intuition and less intellectual humility.